Pengaruh Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis dan Sikap Ilmiah Peserta Didik di SMA Daerah Pedesaan Aceh - Zulfa Yulia; Das Salirawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine differences in critical thinking skills between students who apply the problem-based learning model and students who apply the direct instruction model; Differences in scientific attitudes between students who apply the problem-based learning model and students who apply the direct instruction model. This study uses a quasi-experimental research type with a posttest only design. This research was conducted at SMA Negeri 2 Nisam Aceh Utara. The sample in this study consisted of two classes, namely class XI-IPA1 as the experimental class with the Problem based learning model and class XI-IPA 2 as the control class with the direct instruction learning model. A total of 50 students as the research sample were taken by cluster random technique. The instrument used is in the form of multiple-choice questions to measure students' critical thinking skills and scientific attitude questionnaires. The MANOVA test is used to analyze differences in critical thinking skills and scientific attitudes of students in the experimental class and the control class. The results of the study show that there are significant differences in the ability to think critically between students who apply the problem-based learning model and students who apply the direct instruction model; there is a significant difference in scientific attitude between students who apply the problem-based learning model and students who apply the direct instruction model.